Pengaruh Penting Negosiasi Pencicilan Dan Pelacakan Aset Terkait Penyelesaian Uang Pengganti Dalam Undang-Undang Nomor 3 Tahun 1971 - Yohana Sekar Pawening; Ahmad Ahsin Thohari (Jurnal Relasi Publik, 2024)
Settlement of Money in Lieu aims to provide legal certainty for arrears of Money in Lieu decided by the Court as an additional punishment against the convicted person in a corruption case based on Law Number 3 of 1971 concerning Eradication of Corruption and the decision is legally binding. The author will write about the importance of negotiation and asset tracking related to Non Litigation Settlement of Money in Lieu. The research method between quantitative methods and qualitative methods to be used together in a research activity, so as to obtain comprehensive, valid, reliable and objective data. This is related to the ability of the convict or ex-convict or heirs who have arrears of compensation money to immediately resolve the arrears, which are stated in the Minutes of Negotiations conducted by the State Attorney Team of the work unit and the findings of Asset Tracking. This can be an income in the Central Government that does not come from tax revenues (PNBP) related to State Finance.